Bioremoval of Yttrium (III), Cerium (III), Europium (III), and Terbium (III) from Single and Quaternary Aqueous Solutions Using the Extremophile Galdieria sulphuraria (Galdieriaceae, Rhodophyta) - Manuela Iovinella; Francesco Lombardo; Claudia Ciniglia; Maria Palmieri; Maria Rosa di Cicco; Marco Trifuoggi; Marco Race; Carla Manfredi; Carmine Lubritto; Massimiliano Fabbricino; Mario De Stefano; Seth J. Davis (Plants, 2022)
The lanthanides are among the rare earth elements (REEs), which are indispensable constituents of modern technologies and are often challenging to acquire from natural resources. The demand for REEs is so high that there is a clear need to develop efficient and environmentally-friendly recycling methods. In the present study, living cells of the extremophile Galdieria sulphuraria were used to remove four REEs, Yttrium, Cerium, Europium, and Terbium, from single- and quaternary-metal aqueous solutions. Two different strains, SAG 107.79 and ACUF 427, were exposed to solutions buffered at pH 2.5, 3.5, 4.5, and 5.5. Our data demonstrated that the removal performances were strain and pH dependent for all metal ions. At lower pH, ACUF 427 outperformed SAG 107.79 considerably. By increasing the pH of the solutions, there was a significant surge in the aqueous removal performance of both strains. The same trend was highlighted using quaternary-metal solutions, even if the quantities of metal removed were significantly lower. The present study provided the first insight into the comparative removal capacity of the Galdieria sulphuraria strains. The choice of the appropriate operational conditions such as the pH of the metal solutions is an essential step in developing efficient, rapid, and straightforward biological methods for recycling REEs.